INNOVATIVE APPROACHES TO TEACHING SPEAKING: A CASE STUDY OF SHORT FILM PROJECTS - Tumanggor, Orli Binta (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2023)
This study aims to investigate students' speaking performances in short film projects and their perspectives on these projects. The research involved seventy-seven second-semester students from three classes in the Multimedia Graphic Engineering Technology program at Politeknik Negeri Medan. This research employed a descriptive qualitative research design, collecting data through observation, questionnaires, and interviews. The study evaluates students' speaking abilities, considering indicators such as range, accuracy, fluency, interaction, and coherence. Additionally, it explores students' perspective regarding the use of short film projects as a final assessment in their English subject. The research findings indicate that the majority of students typically reach a C1 level across various speaking descriptors, demonstrating a strong command of the language with room for improvement in specific areas. From the students' perspectives, it becomes evident that short film projects offer several advantages, including the stimulation of critical and creative thinking, the promotion of teamwork, the development of technical multimedia skills, and enhanced confidence in English communication. Nevertheless, the study acknowledges the existence of challenges, such as time constraints and the need for access to equipment and resources. Nonetheless, the integration of short film projects into graphic engineering multimedia classes emerges as a promising approach to enhance English language learning while enriching students' skills and experiences.